2021
DOI: 10.1177/1073858421992265
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Mechanisms in Parkinson’s Disease: From Pathogenesis to Targeted Therapies

Abstract: Inflammation is a critical factor contributing to the progressive neurodegenerative process observed in Parkinson’s disease (PD). Microglia, the immune cells of the central nervous system, are activated early in PD pathogenesis and can both trigger and propagate early disease processes via innate and adaptive immune mechanisms such as upregulated immune cells and antibody-mediated inflammation. Downstream cytokines and gene regulators such as microRNA (miRNA) coordinate later disease course and mediate disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 188 publications
0
11
0
Order By: Relevance
“…Progressive loss of midbrain dopaminergic neurons in the substantia nigra and axonal terminals in the striatum gives rise to characteristic motor disturbances [ 24 ]. Although the underlying mechanisms are still unknown, increasing studies report neuroinflammation as a crucial factor in the pathogenesis of PD, evidencing that inflammatory factors are closely related to the dopaminergic neuron loss in PD [ 25 , 26 ]. For this reason, targeting neuroinflammation may provide neuroprotection in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive loss of midbrain dopaminergic neurons in the substantia nigra and axonal terminals in the striatum gives rise to characteristic motor disturbances [ 24 ]. Although the underlying mechanisms are still unknown, increasing studies report neuroinflammation as a crucial factor in the pathogenesis of PD, evidencing that inflammatory factors are closely related to the dopaminergic neuron loss in PD [ 25 , 26 ]. For this reason, targeting neuroinflammation may provide neuroprotection in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of TAGLN3 have not been reported in patients with PD or T2D. The pathogeneses of PD and T2D both involve inflammatory processes [46,47]. NF-κB plays a major role in the etiology of neurodegenerative disease and T2D [48].…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason is the inconsistency in inclusion criteria: they included data from all types of machines, while we only included data acquired from Siemens' machines; Another possible reason is the inconsistency in analysis methods: they combined deformation-based morphometry and independent component analysis, focusing more on network structure, while we used surface-based morphometry and voxel-based morphometry methods, focusing more on brain region structures. Some researchers believe that "compensated hyperplasia" appears in specific brain regions in early PD, which might be related to the compensatory neuroinflammatory response 30,31 . Astrocytes are activated by proinflammatory cytokines, resulting in cell hypertrophy, astrocyte proliferation, protrusion extension, and interlacing, which leads to increasing surface area and/or thickness of the cortex 32 .…”
Section: Discussionmentioning
confidence: 99%